Estudo da paratuberculose em vacas leiteiras no Rio Grande do Sul - Setim, Diorges Henrique (2020)
Bovine paratuberculosis causes incurable chronic diarrhea, decreased production and withering. It is aused by Mycobacterium avium subsp. paratuberculosis, a mycobacterine dependent mycobacterium, mandatory intracellular, with slow replication in the host and high environmental resistance. In countries that harbor the disease and quantify the damage, the losses are extremely high, directly and indirectly. In order to implement a control program, obtaining local epidemiological data is essential. Thus, a prospective observational cross-sectional study was carried out. Milk samples collected individually from commercial farm cows were tested by an indirect ELISA and classified as negative, suspicious and positive. The disease proved to be detected in two of the five mesoregions tested, obtaining 20 seroreactive cows out of the 362 tested. Together with information from herds, it was found that expansion tank samples can be used for screening and monitoring this disease, in addition to the size of the herd that contributes to greater detection of positive cows.